Expression of yeast DNA topoisomerase I can complement a conditional-lethal DNA topoisomerase I mutation in Escherichia coli. - Bjornsti, M A (1987)
We show that, despite differences in primary structure, substrate preference, and mechanism of catalysis, yeast DNA topoisomerase I can functionally substitute for Escherichia coli DNA topoisomerase I. A family of plasmids expressing the yeast TOP1 gene or 5'-deletion mutations of it were used to complement the temperature-sensitive phenotype of an E. coli topA mutant. These plasmids were then isolated from the cells by a rapid lysis procedure and examined for their degrees of supercoiling. Functional complementation of a conditional-lethal mutation in topA, which encodes E. coli DNA topoisomerase I, correlates with the expression of a catalytically active yeast enzyme that reduces the degree of negative supercoiling of intracellular DNA. We also show that approximately 130 amino acids of the amino-terminal portion of the yeast enzyme can be deleted without affecting its activity in vitro; activity of the enzyme inside E. coli, however, is more sensitive to such deletions.